Mechanical and Thermal Behavior of Cu84-xAl13Ni3Hfx Shape Memory Alloys - Qader, Ibrahim Nazem; Oner, Ecem; Kok, Mediha; Mohammed, Safar Saeed; Dagdelen, Fethi; Kanca, Muhammed Sait; Aydogdu, Yildirim (Springer Int Publ Ag, 2021)
The physical characteristics of a shape memory alloy can be controlled by different production techniques and the rate of constituents' contribution. In this study, CuAlNiHf shape memory alloys, with three different amounts of Hf, were produced by the induction melting method. Many measurements such as differential scanning calorimetry (DSC), scanning electron microscope, energy dispersive X-ray, and the stress-strain test were carried out. The DSC measurement showed that the austenite transformation temperatures were decreased by doping more amount of hafnium into the alloy. All specimens showed a wide temperature hysteresis, which decreased by increasing Hf content. Also, the elastic modulus was raised by increasing the Hf amount. Although gamma(1)' and beta(1)' are the dominant phases in the CuAlNiHf with low Hf composition, substituting Cu with Hf enhanced the amount beta(1)'-phase compared to gamma(1)'-phase.
Keywords: Shape memory alloy; CuAlNiHf; Microhardness; Phase transformation; Thermodynamics parameters